Expression of Recombinant Plasmodium falciparum Cysteine-rich Protective Antigen (PfCyRPA) Fragment 26–181 in Escherichia coli BL21 CodonPlus (DE3) RIPL - Fifi Fitriyah Masduki; Aurelia Galih Prameswari; Fernita Puspasari; Ihsanawati Ihsanawati; Dessy Natalia (Indonesian Society for Biochemistry and Molecular Biology, 2025)
Background: Malaria is a life-threatening infectious disease caused by Plasmodium parasites, transmitted through infected female Anopheles mosquitoes. PfCyRPA (Plasmodium falciparum Cysteine-Rich Protective Antigen) has emerged as a promising vaccine candidate due to its ability to elicit inhibitory antibodies against parasite growth. Objective: This study aimed to construct recombinant plasmids encoding PfCyRPA fragment 26–181 and express this fragment in Escherichia coli BL21 CodonPlus (DE3) RIPL for cost-effective antigen production. Methods: The PfCyRPA gene fragment ( 480 bp) was amplified from P. falciparum genomic DNA (Jayapura isolate) by PCR. Recombinant plasmids pGEM-T-PfCyRPA 26-181 and pET-16b-PfCyRPA 26-181 were constructed and confirmed via colony PCR, restriction analysis, and sequencing. The pET-16b-PfCyRPA 26-181 was transformed into E. coli BL21 CodonPlus (DE3) RIPL. Protein expression was induced with 0.5 mM IPTG at 37°C, and analyzed by SDS-PAGE and Western blotting. Results: SDS-PAGE and Western blot analysis demonstrated successful expression of recombinant PfCyRPA fragment 26–181 with a molecular mass of approximately 21.53 kDa, corresponding to the predicted size. The protein was predominantly expressed as inclusion bodies, typical for eukaryotic proteins in prokaryotic systems. Colony PCR and sequencing confirmed correct gene insertion and integrity. Conclusion: Recombinant PfCyRPA fragment 26–181 was successfully expressed in E. coli BL21 CodonPlus (DE3) RIPL, providing a cost-effective platform for large-scale antigen production. This work establishes a foundational protocol for further immunogenicity research and supports development of this antigen as a potential blood-stage malaria vaccine candidate.